PERLINDUNGAN HUKUM TERHADAP NARAPIDANA DALAM RANGKA PENCEGAHAN DAN PENANGANAN CORONA VIRUS DESEASE (COVID-19) - Abdul Gafur Gafur (Dinamika, 2021)
ABSTRACTThe correctional institution is a place to carry out training for prisoners and students. However, at the time of the covid-19 outbreak, a circular from the director general of prisons was issued by temporarily suspending guidance, as a form of protection for inmates. whereas from several regulations previously related to the existence of an infectious disease, none of them regulated the termination of guidance. Philosophically, the issuance of the circular of the director general of prisons has taken into account the situation that the cases of the spread of the Covid-19 outbreak continue to increase, so that the director general of prisons acts as the one responsible for the situation in prisons and continues to coordinate with the minister of law and ham (as overseeing the correctional institution). In the case of the issuance of the circular of the director general of prisons, the continuity of life in prisons has changed from the pattern of life, both from a temporary suspension of guidance and termination of visiting services.Keywords: Prisoners protection, development, Covid-19. ABSTRAK Lembaga pemasyarakatan merupakan tempat untuk melaksanakan pembinaan narapidana dan anak didik. Namun pada saat adanya wabah covid-19 di keluarkannya surat edaran dirjen lembaga pemasyarakatan dengan memberhentikan sementara waktu pembinaan, sebagai bentuk perlindungan terhadap narapidana. padahal dari beberapa peraturan yang sebelumnya terkait adanya suatu penyakit menular tidak ada yang mengatur tentang pemberhentian pembinaan. Secara filosofis di keluarkannya surat edaran dirjen lembaga pemasyarakatan tersebut telah menimbang dari situasi yang semakin hari kasus menyebaran wabah covid-19 terus bertambah, sehingga dirjen lembaga pemasyarakatan bertindak sebagai yang bertanggung jawab atas keadaan yang berada dalam lembaga pemasyarakatan dan terus saling berkoordinasi dengan menteri hukum dan ham (selaku yang menaungi lembaga pemasyarakatan). Dalam hal pengeluaran surat edaran dirjen lembaga pemasyarakatan tersebut, keberlangsungan kehidupan di dalam lembaga pemasyarakatan mengalami perubahan dari pola kehidupan, baik dari pemberhentian sementara pembinaan dan penghentian pelayanan kunjungan.Kata kunci : Perlindungan narapidana, Pembinaan, Covid-19.